Extrapulmonary Tuberculosis Study at «Daniel A. Carrión Hospital» 1990-1995. - Ynami, Víctor (1996)
The aim of this prospective study was to demostrate that frequency of extrapulmonary tuberculosis at Daniel A. Carrión Hospital is higher than the one reported in the literature. We reviewed The Tuberculosis Control Program Registry and in-patient records from January 1990 to December 1995 . Patients with HIV co-infection were excluded. We fomad 3,304 cases of tuberculosis, 2,301 pulmonaryTBC (69.65%) and 1,003 extrapulmonary cases. Among extrapulmonary TBC, 629 (62.71%) were males and 374 (37.29%) to females.The most important sites were pleural (48.75%), lymphmodal (14.86%) and meningoencephalic (7.68%). We conclude that extrapulmonary TBC at HNDAC is higher than that reported in the national and foreign literature even without HIV co-infection. Prospective reports will be very important to evaluate the final evolution of this group of patients.